A Philosophical Overview of the Government's Role in the Development and Development of the Sharia Economy - Nashoh, Hilmun; Wadud Nafis, Abdul; Is’adi, Munir (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to conduct a philosophical review of the role of government in the development and development of the shariah economy. In the context of the shariah economy, the role of the government is considered important in regulating and encouraging the growth of the economic sector based on the principles of shariah. This research will explore the philosophy behind government intervention in facilitating the development of the shariah economy, as well as its implications for society and economic development as a whole. Using a philosophical approach, this research will analyze the moral, ethical and philosophical aspects underlying the government's role in supporting the shariah economy, as well as how it integrates the values of justice, sustainability and social welfare in sustainable economic development. This research is expected to provide a deeper understanding of the essence and urgency of the government's role in the development of the shariah economy, as well as its contribution to creating a just, sustainable and prosperous society based on the principles of shariah.